Thom Roberts Reads Crowns: Musing on Art and Neurodiversity through the Lens of One Artist’s Practice - Watfern, Chloe (Art/Research International, 2021)
At Studio A, a supported studio for neurodiverse artists, the prolific painter, performer, photocopier, and installation artist Thom Roberts frequently reaches out to connect with friends and fellow artists by running his hands across the backs of their heads; “reading” their crowns. It’s a blessing I have been lucky enough to receive countless times over the course of my ethnographic engagement with Studio A, and as my relationship with Thom has developed. During my research, I have witnessed Thom read crowns in all kinds of contexts, from pubs to art galleries, in a performance artwork that could also be understood as an experimental artist talk. Here, I trace the narrative of this facet of Thom’s practice. I consider how such embodied encounters have the potential to open avenues of communication and connection between people who might experience the world in very different ways.